Storm-Time Evolution of the Equatorial Electron Pitch Angle Distributions in Earth’s Outer Radiation Belt - Smirnov, Artem; Shprits, Yuri; Allison, Hayley; Aseev, Nikita; Drozdov, Alexander; Kollmann, Peter; Wang, Dedong; Saikin, Anthony A. (Frontiers in Astronomy and Space Sciences, 2022)
In this study, we analyze the storm-time evolution of equatorial electron pitch angle distributions (PADs) in the outer radiation belt region using observations from the Magnetic Electron Ion Spectrometer (MagEIS) instrument aboard the Van Allen Probes in 2012-2019. The PADs are approximated using a sum of the first, third, and fifth sine harmonics. Different combinations of the respective coefficients refer to the main PAD shapes within the outer radiation belt, namely the pancake, flat-top, butterfly, and cap PADs. We conduct a superposed epoch analysis of 129 geomagnetic storms and analyze the PAD evolution for day and night MLT sectors. PAD shapes exhibit a strong energy-dependent response. At energies of tens of keV, the PADs exhibit little variation throughout geomagnetic storms. Cap PADs are mainly observed at energies <300 keV, and their extent in L shrinks with increasing energy. The cap distributions transform into the pancake PADs around the main phase of the storm on the nightside and then come back to their original shapes during the recovery phase. At higher energies on the dayside, the PADs are mainly pancake during pre-storm conditions and become more anisotropic during the main phase. The quiet-time butterfly PADs can be observed on the nightside at L>5.6. During the main phase, butterfly PADs have stronger 90°-minima and can be observed at lower L-shells (down to L=5), then transitioning into flat-top PADs at L 4.5-5 and pancake PADs at L<4.5. The resulting PAD coefficients for different energies, locations, and storm epochs can be used to test the wave models and physics-based radiation belt codes in terms of pitch angle distributions.